Forensic entomology an introduction - Gennard, Dorothy E. (Wiley-Blackwell, 2012)
Forensic Entomology provides undergraduates with a concise introduction to the subject. The book is written with the clarity necessary for students starting out in entomology yet authoritative enough to prove useful for more experienced researchers. Assuming little prior knowledge of either biology or entomology the book provides information on identification, life cycles and ecology of insects presented in a forensic context. Information is conveyed in an accessible style with practical tasks and suggestions for further reading included in each chapter.